Renewable energy development in Malaysia: Communication barriers towards achieving the national renewable energy target. Issue 1 (April 2020) - Khairudin, Noor Faezah; Bidin, Rosmiza; Shamsuddin, Abd Halim; Akhiar, Afifi; Ideris, Fazril; Rahman, Adlansyah Abd
Abstract: In Malaysia, the utilization of renewable energy (RE) as in "five fuel diversification policy" has been intensified since 2000 in the 8 th Malaysian plan (2001-2005) as an addition to the supply from conventional energy sources. However, the RE goal in the policy was achieved minimally and later continued in the 9 th Malaysian plan (2006-2010). At the end of 2010, The RE goal was again achieved minimally. Previous studies have been carried out to understand the influence of technological, economic, social and political barriers to the development of renewable energy in Malaysia, but not much on the communication barriers. Therefore, this paper will thoroughly examine the perceptions and understandings on the communication barriers towards renewable energy development in Malaysia.